Standardization of pediatric uroradiological terms: A multidisciplinary European glossary. Issue 6 (December 2017) - Vivier, Pierre-Hugues; Augdal, Thomas A.; Avni, Fred E.; Bacchetta, Justine; Beetz, Rolf; Bjerre, Anna K.; Blickman, Johan; Cochat, Pierre; Coppo, Rosana; Damasio, Beatrice; Darge, Kassa; El-Ghoneimi, Alaa; et al.
Summary: To promote the standardization of nephro-uroradiological terms used in children, the European Society of Pediatric Radiology uroradiology taskforce wrote a detailed glossary. This work has been subsequently submitted to European experts in pediatric urology and nephrology for discussion and acceptance to improve the quality of radiological reports and communication among different clinicians involved in pediatric urology and nephrology.